Similar outcome of upfront‐unrelated and matched sibling stem cell transplantation in idiopathic paediatric aplastic anaemia. A study on behalf of the UK Paediatric BMT Working Party, Paediatric Diseases Working Party and Severe Aplastic Anaemia Working Party of EBMT. (28th July 2015) - Dufour, Carlo; Veys, Paul; Carraro, Elisa; Bhatnagar, Neha; Pillon, Marta; Wynn, Rob; Gibson, Brenda; Vora, Ajay J.; Steward, Colin G.; Ewins, Anna M.; Hough, Rachael E.; de la Fuente, Josu; et al.
Summary: We explored the feasibility of unrelated donor haematopoietic stem cell transplant (HSCT) upfront without prior immunosuppressive therapy (IST) in paediatric idiopathic severe aplastic anaemia (SAA). This cohort was then compared to matched historical controls who had undergone first‐line therapy with a matched sibling/family donor (MSD) HSCT ( n  = 87) or IST with horse antithymocyte globulin and ciclosporin ( n  = 58) or second‐line therapy with unrelated donor HSCT post‐failed IST ( n  = 24). The 2‐year overall survival in the upfront cohort was 96 ± 4% compared to 91 ± 3% in the MSD controls ( P  = 0·30) and 94 ± 3% in the IST controls ( P  = 0·68) and 74 ± 9% in the unrelated donor HSCT post‐IST failure controls ( P  = 0·02).The 2‐year event‐free survival in the upfront cohort was 92 ± 5% compared to 87 ± 4% in MSD controls ( P  = 0·37), 40 ± 7% in IST controls ( P  = 0·0001) and 74 ± 9% in the unrelated donor HSCT post‐IST failure controls ( n  = 24) ( P  = 0·02). Outcomes for upfront‐unrelated donor HSCT in paediatric idiopathic SAA were similar to MSD HSCT and superior to IST and unrelated donor HSCT post‐IST failure. Front‐line therapy with matched unrelated donor HSCT is a novel treatment approach and could be considered as first‐line therapy in selected paediatric patients who lack a MSD.